La relación entre el registro β de la epigrafía anfórica olearia bética y la onomástica de las inscripciones gaditanas altoimperiales - Morales Muñoz, Cristina María (Gerión. Revista de Historia Antigua, 2005)
The presence of Baetican olive oil in Rome and other places of the Empire can be related to families and persons settled in the conventus Gaditanus, specifically in the zone of Cadiz’s present province. Through the comparative study between the mercatores’ tria nomina appeared in the registers β of the tituli picti of Dr. 20 and the tria nomina of the Roman inscriptions from Cadiz, it is possible to establish a serie of family ties between themselves.